Nazım Hikmet: Poet of Revolution and Nationalism - MELKONYAN, RUBEN (Bulletin of Yerevan University B: Philology, 2021)
Poetry, traditionally having leading positions in Oriental literature, had an important place in the Ottoman/Turkish literature until the end of XIX century, too. Principles and traditions, being mostly adopted from the Persian poetry and also including elementsimitated from Western literature, continued to exist with some slight changes till the beginning of XX century. Formation and development of the poetry in the Republic of Turkey and inclusion of the subject of revolution in it is associated with the name of Turkish poet Nazım Hikmet. Being famous among literary critics as “first Turkish communist” poet or founder of socialist style in Turkish literature, Nazım Hikmet at the same time had a contradictive personality which is reflected in his literary work as well as in public and political activity. Although in his works Nazım Hikmet touched on the problem of equality of nations, opposed social and ethnic discrimination, he kept silence or nearly didn’t speak about genocides, suppressions against non-Turks in Turkey taking place in the past and continuing in his lifetime. Besides, he adopted nationalistic and even racist approaches to the range of problems both in his works and public activity.
Keywords: Turkish poetry, subject, genre, character, “free verse”, nationalism, racism, Armenian Genocide, Pan-Turkism, Communism